Malaria crystalloids: specialized structures for parasite transmission? - Dessens, Johannes T. (Elsevier Science, 2011)
Malaria parasites possess many unique subcellular structures and organelles that are essential for the successful completion of the complex life cycle of Plasmodium in the vertebrate host and mosquito vector. Among these are the crystalloids: transient structures whose presence is restricted to the mosquito-specific ookinete and young oocyst stages of the parasite. Nearly five decades after they were first described, the crystalloids are back in the spotlight, with recent discoveries pointing to an important role in protein trafficking and sporozoite transmission that could be exploited as new targets for control of malaria transmission.